Marine Fish Marketing and Prices Changes in Different Levels of Market in Bangladesh: An Empirical Study Using Primary Data (The Agriculturists, 2018)
Contribution of fisheries in the national economy of Bangladesh is substantial, particularly with reference to food consumption, nutrition, employment and export. The present study was designed to determine the changes of prices of marine fish at different levels of market and to determine various problems relating to marine fish marketing system in Bangladesh. This study used purposive sampling and data were collected from 168 stakeholders using interview schedule considering 10 major species of marine fish during 2014. Primary, secondary and consumer market were considered in the study. The study revealed that both marketing margins as well as marketing profit are relatively higher in consumer market followed by primary and secondary markets, where baparis and aratders are involved. Marketing costs for per kg of marine fish were estimated to be Tk 8.55, 1.10 and 4.50 for beparis, aratdars and retailers, respectively. Average marketing cost was lower in primary market (Tk 8.86/kg) compared to secondary market (Tk 9.99/kg) and consumer market (Tk 12.29/kg). The marketing system of marine fish in Bangladesh is yet to be developed and since this is facing a lot of problems including post-harvest losses, poor physical facilities, etc. Government and department of fisheries should take necessary action for development of marketing system of marine fishes.The Agriculturists 2017; 15(2) 79-87